2023
DOI: 10.1002/efd2.118
|View full text |Cite
|
Sign up to set email alerts
|

Zhenjiang aromatic vinegar prevents the alcohol liver disease in mice via autophagy

Yuxuan Zhao,
Ting Xia,
Xiao Qiang
et al.

Abstract: Alcoholic liver disease (ALD) is an ignored global issue of public health. It is urgent for searching bioactive foods to prevent ALD. Zhenjiang aromatic vinegar (ZAV) contained antioxidant compounds, including polyphenols, flavonoids, and melanoidins. The mechanism of ZAV on preventing acute liver injury was evaluated in alcohol‐treated mice. Our results showed that ZAV ameliorated morphological damage by hematoxylin and eosin and Oil Red O staining in alcohol‐treated liver. ZAV relieved symptoms of ALD, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…First, autophagy can remove oxidative stress products and inflammatory factors within cells, thereby reducing vascular endothelial damage and inflammatory response and helping to slow down the development of atherosclerosis. Second, autophagy also regulates lipid metabolism, helping to prevent the formation of atherosclerotic plaques by clearing cholesterol and lipid deposits …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, autophagy can remove oxidative stress products and inflammatory factors within cells, thereby reducing vascular endothelial damage and inflammatory response and helping to slow down the development of atherosclerosis. Second, autophagy also regulates lipid metabolism, helping to prevent the formation of atherosclerotic plaques by clearing cholesterol and lipid deposits …”
Section: Discussionmentioning
confidence: 99%
“…Second, autophagy also regulates lipid metabolism, helping to prevent the formation of atherosclerotic plaques by clearing cholesterol and lipid deposits. 30 Studies have shown that Schisandrin C can affect autophagy by regulating the activity of PI3K/AKT/mTOR pathway. mTOR plays an important regulatory role in autophagy and is the main negative regulatory axis of autophagy.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During alcohol metabolism, steatosis can be induced, resulting in fat deposition in liver cells. Meanwhile, alcohol affects the transport of blood lipids, leading to abnormal levels of serum TG and TC (Qi et al, 2023;Zhao et al, 2023). Research conducted on ALD mice has shown that alcohol significantly elevates TC, TG, and LDL-C levels in serum while decreasing HDL-C levels, thereby causing lipid accumulation in the liver (Shen et al, 2014).…”
Section: Effects Of Inulin On Serum Indexes Of Mice With Acute Alcoho...mentioning
confidence: 99%